A geometric approach to modeling of four- and five-link planar snake-like robot. (12th October 2016) - Lipták, Tomáš; Virgala, Ivan; Frankovský, Peter; Šarga, Patrik; Gmiterko, Alexander; Baločková, Lenka
The article deals with the issue of use of geometric mechanics tools in modelling nonholonomic systems. The introductory part of the article contains fiber bundle theory that we use at creating mathematical model of nonholonomic locomotion system with undulatory movement. Further the determination of general mathematical model for n -link snake-like robot is presented, where we used nonholonomic constraints. The relation between changes of shape and position variables was expressed using the local connection that was used to analyze and control system movement by vector fields. The effect of links number of snake-like robot on its mathematical model was investigated. The last part of this article consists of detailed description of modeling reconstruction equation for four - and five -link snake-like robot.